Handling stability analysis of decoupling suspension for formula racing - Xu, Han; Xu, Jiachuan; Cui, Xuemin; Zhou, Yang; Sun, Xinyu; Wang, Zongqi (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
In this paper, a university formula racing suspension is taken as the research object. Based on the requirements of racing suspension, the double wishbone suspension is improved, and a new arrangement scheme based on the stepped shaft is proposed, which theoretically realizes the decoupling of the pitch stiffness and the roll stiffness of the suspension. Based on the ADAMS/Car module, the front and rear suspension models are established. By simulating the motion of formula racing, it is further judged whether the pitch and roll stiffness of the suspension are decoupled. According to this, the hard point coordinates of the suspension are adjusted to ensure that the length of each spring changes within the ideal range. Based on the optimized suspension, according to the national standard test method and the scoring standard of the automobile industry, combined with the university formula racing project, the vehicle handling stability test and scoring evaluation are carried out, and the vehicle handling stability is verified by the real vehicle test. A set of decoupling suspensions is obtained, which can have pitch stiffness and roll stiffness separately adjusted, with improved vehicle handling stability.